The Effect Of Education On Community Knowledge Level Regarding Pre-Hospital Management Of Bleeding Wound Cases - Samsir Samsir; Alamsyah Alamsyah; Zainuddin Zainuddin; Muh. Babul Fahri (Proceeding of the International Conference on Health Sciences and Nursing, 2025)
Background: Bleeding is one of the emergency conditions that can be life-threatening if not treated quickly and appropriately, especially at the pre-hospital stage. Poor public knowledge regarding the initial management of bleeding cases is a risk factor for increased morbidity and even mortality. Objective: To determine the effect of health education on improving public knowledge regarding pre-hospital management of bleeding in wounds. Methods: This study used a pre-experimental design with a one-group pretest-posttest approach. A sample of 96 respondents was selected through purposive sampling technique. The intervention in the form of health education was provided through lectures, discussions, and leaflets. Data were collected using questionnaires and analyzed using the Wilcoxon test. Results: There was a significant increase in the level of public knowledge after health education was provided (p = 0.000). Conclusion: Health education significantly influences the improvement of public knowledge regarding pre-hospital management of bleeding wound cases.